Construção territorial dos imigrantes italianos no distrito de Arroio Grande, Santa Maria/RS - Marchezan, Jorge (2024)
The occupation of the territory of Rio Grande do Sul was supported by European immigrants in different periods of time. Here, we will emphasize aspects related to their arrival in Brazil, Rio Grande do Sul, Silveira Martins founding the Quarta Colônia of Italian Immigration and, later, Santa Maria, especially the District of Arroio Grande. Based on the problem, District of Arroio Grande: Territory of Santa Maria? The aim was to understand the territorialization of Italian immigrants in Arroio Grande, Santa Maria, Rio Grande do Sul, Brazil through the materialized heritage in the territory. To this end, we will retrieve the oral history of residents of Arroio Grande, interviewed in 2015, retracing the history of their reterritorialization in the District of Arroio Grande, in Santa Maria, based on their narratives. The research carried out in 2015 (final work for the Bachelor's Degree in Geography) is deepened in the years 2020 to 2024 in the Master's Course in the Postgraduate Program in Geography at UFSM, reinserting it into the discussion of the territory. The methodological approach of the research is based on qualitative research, whose techniques are substantiated with the use and analysis of archives and photographic records, bibliography, fieldwork and the narratives of the interviewed residents. In the territorial organization, the District of Arroio Grande belongs to Santa Maria, but with regard to geohistorical and heritage issues, it is related to Italian immigration in Brazil, specifically the Quarta Colônia, and with this, it validates the existence of territorial expressions of the Italian presence in Brazil in Santa Maria/RS.